(untitled) (Journal of Atomic and Molecular Sciences, 2016)
Wigner function is a fundamental method to study the connection between quantum and classical system. Since negative value can be accepted by Wigner function even from a positive initial condition, they are various issues existing in corresponding interpretation as well as the development of numerical methods. We present the entangled trajectories based on the Wigner distributions with negative values.